Criminology and genocide studies: notes on what might have been and what still could be - Day, L. Edward (Crime, law and social change, 2000)
Scholars of genocide and mass killings have proposed several theories explaining how the behaviors of governments, political leaders, and ordinary citizens contribute to extreme violence. Many of the explanatory constructs developed in these theories bear a striking resemblance to core concepts of criminology or could be readily integrated with criminological ideas. As examples, this paper briefly describes the ideas of Herbert Kelman, Daniel Jonah Goldhagen, and R.J. Rummel from the perspective of criminology and examines their applicabilitythe recent genocides in Bosnia and Rwanda. The conclusion is that criminology, by largely ignoring the crime of genocide, has missed opportunities to both contribute to the field of genocide studies and to improve the specification of its own ideas.